2015
DOI: 10.1021/acs.jproteome.5b00588
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the CHO Super-Ome (CHO-SO) by Proteoinformatics

Abstract: Chinese hamster ovary (CHO) cells are the preferred host cell line for manufacturing a variety of complex biotherapeutic drugs including monoclonal antibodies. We performed a proteomics and bioinformatics analysis on the spent medium from adherent CHO cells. Supernatant from CHO-K1 culture was collected and subjected to in-solution digestion followed by LC/LC–MS/MS analysis, which allowed the identification of 3281 different host cell proteins (HCPs). To functionally categorize them, we applied multiple bioinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 123 publications
2
32
0
Order By: Relevance
“…In addition to the recombinant protein of interest, host cells spend a substantial amount of resources on producing other proteins, such as host cell proteins133132. Indeed, our cell lines demonstrated that ~90% of the ribosomal occupancy is spent on proteins other than the desired IgG (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to the recombinant protein of interest, host cells spend a substantial amount of resources on producing other proteins, such as host cell proteins133132. Indeed, our cell lines demonstrated that ~90% of the ribosomal occupancy is spent on proteins other than the desired IgG (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…GO terms for CHO were obtained using GOCHO13 and terms under the parent term ‘Biological Process’ were extracted and converted into a GMT file according to GSEA manual. A ranked list of genes was made using the expression values obtained from Ribo-Seq quantification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LC‐MS based “omics”‐approaches are increasingly used to gain advanced understanding of biomanufacturing processes such as to study host cell proteins (HCPs), productivity during process scale‐up or cellular response to altered media composition (Farrell et al, ; Gao et al, ; Liu et al, ). The recent elucidation of the CHO cellular and secreted proteome further facilitates research in this area (Baycin‐Hizal et al, ; Kumar et al, ). Advanced LC‐MS technology has therefore also been used to study proteomics changes in relation to CHO cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…CHO cells are well adapted to growing in suspension with different media compositions2. For large-scale commercial production of mAbs, fed-batch culture has been widely used at large scales, up to 20,000 L working volume, because of its operational simplicity and high-titers.…”
mentioning
confidence: 99%